PEMBERDAYAAN PENINGKATAN KAPASITAS USAHA KUE DI KECAMATAN SAMBIKEREP SURABAYA - Abdillah, Khubbi; Edi, Agus Sarwo; Aminatuzzuhro, Aminatuzzuhro (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The partner in this community service activity is Mrs. Endah Yulie Purwatie, as the owner of the Aisyah Cake & Cookies cake business located at Jl. Bringin Harapan 1 No. 3, Bringin Village, Sambikerep District, Surabaya City 60218. The background of the problem in this PPM activity was triggered by: Uncertain partner income due to production equipment that was starting to not function properly (mixer), unattractive product packaging, the cakes sold were still monotonous; partners have not utilized social media; there has been no simple financial record calculation. The objectives of this PPM activity include: (i) Increasing product consistency by updating the mixer, attractive packaging, adding contemporary cake product variants; (ii) Utilizing social media to market cake products; (iii) Recording simple financial reports. The methods used in this PPM activity include: (i) Assistance with standing mixers, packaging assistance, providing product diversification training by adding flavor variations in various types of cakes; (ii) Providing assistance in marketing products through social media; (iii) Providing assistance in making simple financial report records. The results of the activities in this PPM activity include increased production capacity, increased partner skills, and an increase in partner income by 30%